Réponses

2013-05-15T17:11:51+02:00

L = (2x + 3)(5x - 8) - (2x - 4)(5x - 1)

L = 10x² - 16x + 15x - 24 - (10x² - 2x - 20x + 4)

L = 10x² - x - 24 - 10x² + 2x + 20x - 4

L = 21x - 28

 

M = (x + 5)²

M = x² + 10x + 25

 

N = (4 + 7x)²

N = 16 + 56x + 49x²

N = 49x² + 56x + 16

 

P = (4x + 6)²

P = 16x² + 48x + 36

 

S = (x - 5)²

S = x² - 10x + 25

 

T = (3x - 7)²

T = 9x² - 42x + 49

 

U = (1 - 6x)²

U = 1 - 12x + 36x²

U = 36x² - 12x + 1

2013-05-15T17:18:03+02:00

L=(2x +3)(5x -8) -(2x-4)(5x -1)

L = (10x² -16x +15x -24) - ( 10x² -2x -20x +4 )

L = 10x² -x -24 - 10x² +22x -4

L = 21x -28

 

 

 M=(x+5)²

M= x² + 10x + 25

 

N=(4+7x)²

N = 49x² + 56x + 16

 

P=(4x+6)²

P = 16x² + 48x+ 36

 

S=(x-5)²

S = x² - 10x +25

 

T=(3x-7)²

T= 9x² - 42x + 49

 

U=(1-6x)²

U = 36x² -12x +1